2018
DOI: 10.1111/ene.13796
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome is associated with headache‐related disabilities in patients with migraine: a prospective 7‐year follow‐up study

Abstract: Our prospective study showed that RLS had a significant impact on headache-related disability in patients with migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
1
5
0
4
Order By: Relevance
“…In recent years, widespread attention has been paid to the comorbid association between migraine and RLS. This study found that the prevalence of RLS in migraine patients (22.29%) was significantly higher than that in non-headache controls (6.62%), which was consistent with other research findings ( 3 , 6 , 21 , 23 , 24 ). In addition, it has also been found that migraines and RLS affect each other.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In recent years, widespread attention has been paid to the comorbid association between migraine and RLS. This study found that the prevalence of RLS in migraine patients (22.29%) was significantly higher than that in non-headache controls (6.62%), which was consistent with other research findings ( 3 , 6 , 21 , 23 , 24 ). In addition, it has also been found that migraines and RLS affect each other.…”
Section: Discussionsupporting
confidence: 93%
“…Univariate analysis revealed that the monthly days with headache, high PSQI score, high HADS score, and vitamin D deficiency were the risk factors for RLS in patients with migraines. Firstly, in terms of sleep quality, anxiety, and depression, a large number of previous studies have reported that migraine patients complicated with RLS have worse sleep quality and more significant anxiety and depression symptoms than those with migraine alone ( 3 , 7 , 21 , 23 , 24 ). Besides, these clinical factors are related to the occurrence of RLS ( 3 , 7 , 21 ), consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“… 52 The presence of RLS also predicted headache-related disability in migraine patients 7 years later. 77 Although not yet proven, the management of sleep disturbances in migraine, especially RLS, may improve CS in migraine.…”
Section: Methodsmentioning
confidence: 99%
“…Nu sta ty ta, kad di des nis NKS pa pli ti mas yra su si jaes su daþnes niu mig re nos su au ra pa si reið ki mu [8]. Ki tø ty ri mø rezul ta tai pa ro dë, kad NKS simp to mai yra stip res ni ser gantiems mig re na, o ðiø li gø ko mor bi dið ku mas le mia sun kesnae pa cien tø bûk lae [11,35]. Re mian tis li te ra tû ros duo me nimis, ga li ma teig ti, kad mig re na ir NKS ga li ska tin ti vie nas ki to pa si reið ki mà [3,4,11].…”
Section: Paplitimasunclassified
“…Do pa mi nas taip pat da ly vau ja mig re nos pa to fi zio lo gijo je. At lik tuo se ty ri muo se nu sta ty ta, kad ser gan tie ji mig rena yra jaut res ni do pa mi ner gi niams vais tams ir, pa si reið kus mig re nai, ma to mas at virkð ti nis do pa mi no an ta go nis tø povei kis [35,38]. Ma no ma, kad NKS ir mig re na yra su si jae su A11 do pa mi ner gi niu bran duo liu, esan èiu po gum bu ry je (pav.).…”
Section: Patofiziologijaunclassified